Association of Prepregnancy Obesity and Remodeled Maternal-Fetal Plasma Fatty Acid Profiles - Yu, Hai-Tao; Xu, Wen-Hui; Chen, Yi-Ru; Ji, Ye; Tang, Yi-Wei; Li, Yue-Ting; Gong, Jia-Yu; Chen, Yi-Fei; Liu, Guo-Liang; Xie, Lin (Frontiers in Nutrition, 2022)
Background: Fatty acids, especially polyunsaturated fatty acid (PUFA), are found abundantly in the brain and are fundamental for a fetus’s growth. The fatty acid profiles of mothers and fetuses may be affected by maternal pre-pregnancy body mass index (pre-BMI), thus affecting fetal growth and development. Methods: A total of 103 mother–fetus pairs were divided into overweight/obese (OW, n=26), normal weight (NW, n=60), and underweight (UW, n=17) groups according to pre-BMI. Fatty acid profiles in maternal and umbilical cord plasma were analyzed by gas chromatography. Results: The infant birth BMI z-score of the OW group was higher than that of the NW and UW groups (P < 0.05). The OW mothers had significantly higher plasma n-6 PUFA and n-6/n-3, but lower DHA and n-3 PUFA (P < 0.05). In cord plasma, the proportions of docosahexaenoic acid (DHA) and n-3 PUFA were lower in the OW group (P < 0.05), while the n-6/n-3 ratio was higher in the OW group (P < 0.05). The pre-BMI was negatively correlated with cord plasma DHA in all subjects (r = -0.303, P = 0.002), and the same negative correlation can be observed in the OW group (r = -0.561, P = 0.004), but not in the NW and UW groups (P > 0.05). The pre-BMI was positively correlated with cord plasma n-6/n-3 in all subjects (r = 0.325, P = 0.001), and the same positive correlation can be found in the OW group (r = 0.558, P = 0.004), but not in NW and UW groups (P > 0.05). Conclusions: Maternal pre-BMI was associated with the maternal-fetal plasma fatty acid profiles, while the adverse fatty acid profiles are more noticeable in the pre-pregnancy overweight/obesity mothers.